Role of The Halal Industry in Recovering the National Economy in Covid-19 Pandemic - Cucu Susilawati (UIN Sunan Gunung Djati Bandung, 2020)
The outbreak of the Covid-19 pandemic in Indonesia is attacking not only public health but also the economy. The presence of Covid-19 has many important impacts on developed countries. There are at least four industries most impacted by this pandemic, including households, MSMEs, companies and the financial industry. However, the halal industry is believed to be more resilient to the Covid-19 pandemic. This durability is because of the principles attributed to the halal sector, namely the importance of fairness, balance and openness. The author’s goal is therefore to carry out more in-depth research on the role of the halal industry in supporting the national economy, which is under pressure because of the COVID-19 pandemic. This type of study is a literature review with a material analysis approach that explores the conditions of the halal industry in Indonesia in depth. The material received is as books, published information, and online news. The findings of this study reveal that there are three halal business sectors that are believed to be more vulnerable to the Covid-19 pandemic in order to facilitate national economic recovery. Halal finance, halal food and halal fashion industries are among them. Halal finance from both the banking sector and the Islamic stock market has proved to be more robust than the mainstream financial sector. Besides guaranteed halal food, its wellbeing is also guaranteed, and halal fashion is now on the rise as Muslim fashion is increasingly innovative and global. We believe the three of them to have experienced vigorous growth, and also to continue to draw customers. And also after the Covid-19 pandemic, these three sectors could survive. Thus the halal industry also contributes to Indonesian economy.